(untitled) (Research, Society and Development, 2021)
The American Tegumentary Leishmaniasis (ATL) occurs in several parts of the world, in Brazil and also in the State of Parana, it is a disease of great importance in public health, since it affects animals and humans, with a zoonotic character. Leishmaniasis is found in two forms, tegumentary and visceral, and has sandflies as vectors and wild animals and domestic dogs as reservoirs. ATL is considered an endemic disease in the city of Bandeirantes, with human cases occurring in several urban and rural locations, mainly in areas close to forest remnants, peri-urban and peripheral areas, where vulnerable populations live in general, and with precarious basic sanitation conditions. In these regions also live the participants of the wagon driver project, who own several working horses. The project provides guidance on management, good practices, disease prevention, and animal welfare. Since the role of horses as reservoirs and in the chain of transmission of ATL is not well known, the aim of this study was to carry out a serological study of ATL in horses and in the contact dogs of the participants of the " wagon driver" project, at UENP-CLM, to evaluate seropositivity in these species. Blood samples were collected from 20 horses and 12 contact dogs. A serological study, using the ELISAi test for ATL diagnosis, was carried out on the horses and dogs in relation to this study population, to assess seropositivity. In the serological survey, eight horses out of 20 animals (40%) and four dogs out of 12 animals (33.33%) were seropositive, a result considered significant, indicating the presence of the disease and the risk of transmission where they live. The occurrence of human cases and the presence of ATL vectors have already been identified in several locations in the city. Due to the lack of knowledge about the disease and the difficulty in controlling the vectors, health education is necessary in order to provide the population with orientation on how to prevent the disease, as well as entomological surveillance and new serological studies in areas at risk for ATL transmission. The results indicate that there may be importance in the role of horses as reservoirs and in the transmission of Tegumentary Leishmaniasis, which still needs to be clarified.